Penyelesaian Kredit Macet Pada Kredit Tanpa Agunan Di PT. Bank CIMB Niaga, Tbk. Cabang Semarang - Elisa Andriyani, Kashadi*), Herni Widanarti (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Granting credit is one of the Government's efforts to support the rate of development is that development results that must include a program to provide the opportunity for more to the community to be able to develop the business get the fulfillment of his needs through the wisdom of granting credit. To provide convenience for society in terms of credit submission, then the PT Bank CIMB Niaga Tbk of Semarang Branch provided credit without Collateral, credit is given without any guarantee of goods that can be given to anyone, in the sense not constrained in certain economic sectors, particular, membership of certain groups of people, all the prospective customer in question has complied with all its terms and conditions. In practice occasionally occurred the debtor was unable to pay his debts, thus causing the occurrence of bad credit.